Factors Affecting MARPE Success in Adults: Analysis of Age, Sex, Maxillary Width, and Midpalatal Suture Bone Density - Echarri-Nicolás Javier; González-Olmo María José; Echarri-Labiondo Pablo; Olmos-Valverde Marta; Romero Martín (Applied Sciences)
Microimplant-assisted rapid palatal expansion (MARPE) is a technique widely used to treat transverse discrepancies in adult patients. The present study aims to examine how age, sex, maxillary width, and suture bone density might influence MARPE efficacy. It also analyzes bone density variations across the midpalatal suture regions. Materials and Methods: This retrospective study included 30 adult patients who underwent MARPE treatment. Pre- and post-treatment CT scans were analyzed to quantify the maxillary width and bone density measured in Hounsfield units (HUs) in the anterior, middle, and posterior nasal spine regions. Statistical analyses were carried out and included descriptive statistics, t-tests, and effect size calculations. Results: Younger patients (age 22.13 ± 4.58) had significantly higher success rates compared to older patients (aged 25.66 ± 4.67). No significant differences were found regarding sex or the initial maxillary width. Lower bone density in the middle and posterior nasal spine regions was correlated with higher success rates. Data showed that the anterior nasal spine exhibited higher bone density, but this finding did not affect treatment outcomes significantly. Conclusions: Age seems to be a crucial factor in MARPE success, with younger patients showing better outcomes. Regarding bone density, results showed that its values in the middle and posterior nasal spine regions could be a determinant of treatment success. On the contrary, sex and the initial maxillary width did not appear to affect outcomes. These findings emphasize the importance of preoperative assessments and the consideration of individual anatomical variations for optimal MARPE treatment planning.